Effect of cyclonic storm Vardah on the community structure and ecosystem functioning of macrobenthic fauna in the intertidal region of South Andaman Islands - Sahu, Nosad; Lakra, Raj Kiran; Thiruchitrambalam, Ganesh (Frontiers in Marine Science, 2022)
An investigation was carried out to understand the effect of a cyclone Vardah on the functioning of macrobenthos. The assessment was accomplished by comparing before cyclone (BC) and after cyclone (AC) data of macrobenthos. Additionally, temporal changes in the faunal assemblages were evident through multivariate techniques. Five distinguished assemblages could be noticed through the Bray–Curtis similarity representing different phases of the cyclone. The cyclonic effect also resulted in the recruitment of some macrobenthic species and the loss of a few during the study period. Biological trait analysis identified subsurface deposit feeders, upward and downward conveyers, Ecological Group IV, mid-mobile macrobenthos and size class of 2–4 cm as the important groups that dominated the functioning of the macrobenthic community immediately after the cyclone. The resilience and recruitment of macrobenthos were explained using functional redundancy.